Shifting shadows ebook - Briggs, Patricia (Mercy Thompson., 2014)
Shapeshifter Mercy Thompson has friends in high places—and in low, dark, scary ones. And in this must-have collection of short stories, you’ll meet new faces and catch up with old acquaintances—in all their forms... Includes the new stories... “Silver” “Roses in Winter” “Redemption” “Hollow” …and reader favorites “Fairy Gifts” “Gray” “Seeing Eye” “Alpha and Omega” “The Star of David” “In Red, with Pearls” “One of the best urban fantasy anthologies I’ve ever read.”—The BiblioSanctum